Influence of the colony cycle on physiological and morphological caste variation in the perennial neotropical swarm-founding social wasp, Protonectarina sylveirae (Hymenoptera, Vespidae, Epiponini) - Shima, Sulene Noriko [UNESP]; Noll, Fernando Barbosa; Zucchi, Ronaldo (My University, 2003)
This paper describes the influence of the colony cycle on caste differences in Protonectarina sylveirae. Despite invariably keeping the main aspects of the conspicuous dimorphism between the castes, it is shown that: 1- queen-worker differences varied according to the progress of the colony cycle, 2- queens in pre-emergence colonies were smaller than those in male-producing ones, 3- workers were larger in pre-emergence than in other colony stages, 4- at particular steps of the colony cycle, non-inseminated ovary-developed queens and workers were detected. The size of the spermatheca differed between inseminated and non-inseminated queens with the highest values appearing in those bearing the most developed kind of ovary development. Differences between inseminated and non-inseminated queens were found in tergites III and IV, ovarian development and amount of fatty tissues. Because tergite size relates to gaster size, this character may be an important stimulus for selection of larger queens in the course of the colony cycle.
Keywords: Caste differences; Colony cycle; Epiponini; Polistinae; Protonectarina sylveirae; Social wasps; Vespidae; Hymenoptera